2018 IEEE Second International Conference on Data Stream Mining &Amp; Processing (DSMP) 2018
DOI: 10.1109/dsmp.2018.8478613
|View full text |Cite
|
Sign up to set email alerts
|

MEMS-Based Inertial Sensor Signals and Machine Learning Methods for Classifying Robot Motion

Abstract: Robot state classification using machine-learning methods and MEMS sensors data is proposed in the paper. An experiment was performed with a three-axis MEMS gyroscope rigidly fixed to the robot body. In it we investigated the possibilities of various machine-learning methods for solving classification task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…MEMS-IMU has attracted much attention in the recent years owing to their low cost, small size, and ease of integration [ 1 ]. This device is ushering in a huge market demand, as it has become an important component of different navigation systems, attitude control devices [ 2 ], unmanned aerial vehicles [ 3 ], robot navigation [ 4 , 5 , 6 ], satellite systems [ 7 ], etc. MEMS-IMU system is often affected by various factors characterized on environmental, electronic, and manufacturing noises all leading to random navigation errors when using MEMS-IMU [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MEMS-IMU has attracted much attention in the recent years owing to their low cost, small size, and ease of integration [ 1 ]. This device is ushering in a huge market demand, as it has become an important component of different navigation systems, attitude control devices [ 2 ], unmanned aerial vehicles [ 3 ], robot navigation [ 4 , 5 , 6 ], satellite systems [ 7 ], etc. MEMS-IMU system is often affected by various factors characterized on environmental, electronic, and manufacturing noises all leading to random navigation errors when using MEMS-IMU [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to future sensors, artificial intelligence (AI) would unquestionably play a vital role in terms of "decoding" signals from the various sensor system and networks [179][180][181][182][183][184][185][186][187][188]. Furthermore, VR and AR will also rely much on novel sensors to provide better functionality such as immersive experience and feedback control.…”
Section: Mems/nems Vs Ai and Its Vr And Armentioning
confidence: 99%
“…This sensor-related AI system can recognize handwriting and gestures, which successfully demonstrated the application of the next-generation sensors. Nevlydov et al developed a robot using machine-learning methods as shown in Figure 12a [180]. They successfully adopted a three-axis MEMS gyroscope fixed to the robot body using various machine-learning methods for solving classification tasks.…”
Section: Mems Vs Aimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MEMS inertial sensors are widely popular in civil and military applications. According to the application scenario, in the civilian field, MEMS inertial sensors are mainly used in consumer portables such as mobile phones, game consoles, digital cameras, robots, and medical devices for health care [ 9 , 10 , 11 , 12 , 13 , 14 ]. In the military field, MEMS inertial sensors are commonly employed in high-end markets such as optoelectronic devices, aerospace, torpedo, missile, rockets, and so on [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%